2021
DOI: 10.1002/tox.23100
|View full text |Cite
|
Sign up to set email alerts
|

Potential chemotherapeutic effect of betalain against human non‐small cell lung cancer through PI3K/Akt/mTOR signaling pathway

Abstract: This work focuses on evaluating the therapeutic ability of betalain and its causal mechanisms in NSCLC both in vivo and in vitro. The experimental results demonstrated that betalain was able to reduce the viability of A549 cells dose dependently with undetectable toxicity toward normal human cells. Betalain also augmented the apoptotic cells of A549 and cell cycle arrest which was evidenced via increased in level of p53/p21 and decreasing levels of cyclin-D1 complex. Moreover, betalain also reduced the levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 32 publications
0
33
0
1
Order By: Relevance
“…[10][11][12] Nevertheless, therapy for NSCLC is still unsatisfactory. 13,14 A better understanding of the molecular regulation mechanism in NSCLC is required. 15 Recent findings have shown that epigenetics participate in the occurrence and development of tumours.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Nevertheless, therapy for NSCLC is still unsatisfactory. 13,14 A better understanding of the molecular regulation mechanism in NSCLC is required. 15 Recent findings have shown that epigenetics participate in the occurrence and development of tumours.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the mTOR pathway is closely related to tumor proliferation, invasion, and metastasis [13]. Blocking the PI3K/AKT/mTOR signaling pathway can inhibit tumor cell proliferation and metastasis and even induce cell apoptosis [14]. Li et al found that plumbagin can block the PI3K/AKT/mTOR signaling pathway, leading to lung cancer cell apoptosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…Xanthine oxidase is a type of enzyme that generates free radical species and catalyse the oxidation of hypoxanthine to xanthine and oxidation of xanthine to uric acid [9,14-15] and it is generally treated with the standard drugs allopurinol. Allopurinol is a structural isomer of hypoxanthine and is an inhibitor of the enzyme xanthine oxidase.Our team has extensive knowledge and research experience that has translate into high quality publications [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The aim of the study is to evaluate the antioxidant and xanthine oxidase inhibitory potential of methanolic leaf extract of Stevia rebaudiana.…”
Section: Introductionmentioning
confidence: 99%